Assessing The Capability of Disaster Risk Reduction and Management in Marikina City - Guardiano, Hershey Lee A. (Future Science / FSH-PH Publications, 2024)
This study assesses the capability of disaster risk reduction and man-agement (DRRM) in Marikina City, Philippines, aiming to enhance disas-ter resilience through effective implementation of Republic Act 10121 the Philippine Disaster Risk Reduction and Management (DRRM) Act of 2010. The research assesses Marikina City's implementation and chal-lenges across disaster prevention and mitigation, disaster preparedness, disaster response, and disaster recovery and rehabilitation. Utilizing a quantitative methodology, data were collected from Marikina City Disas-ter Risk Reduction and Management Office (MCDRRMO) personnel, ba-rangay officials, and residents to evaluate implementation levels and identify challenges. This research contributes significantly to under-standing local government DRRM capabilities in urban disaster-prone areas. It provides valuable insights for policymakers and practitioners, highlighting effective practices and areas for further improvement. The study found that continuous capacity building, community engagement, and inter-agency collaboration are critical for strengthening Marikina City's resilience. It offers valuable recommendations for local policy-makers and practitioners to address identified challenges and improve DRRM implementation.